2020
DOI: 10.3390/pathogens9060511
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Strongyloidiasis among Latin American Migrants in Spain: A Community-Based Approach

Abstract: Strongyloides stercoralis infection is frequently underdiagnosed since many infections remain asymptomatic. Aim: To estimate the prevalence and characteristics of asymptomatic S. stercoralis infection in Latin American migrants attending a community-based screening program for Chagas disease in Spain. Methodology: Three community-based Chagas disease screening campaigns were performed in Alicante (Spain) in 2016, 2017, and 2018. Serological testing for S. stercoralis infection was performed using a non-automat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…It is important to recognize health inequalities and barriers that migrants and other minority groups have to face to access the US healthcare systems and, subsequently, to be screened and treated. Several experts have pointed out the efficacy of transversal and community-based interventions to deal with NTDs and other diseases [ 22 , 23 ]. It is crucial to adapt the interventions to each collective enhancing the role of primary healthcare settings to overcome those barriers.…”
Section: Other Noncommunicable Diseasesmentioning
confidence: 99%
“…It is important to recognize health inequalities and barriers that migrants and other minority groups have to face to access the US healthcare systems and, subsequently, to be screened and treated. Several experts have pointed out the efficacy of transversal and community-based interventions to deal with NTDs and other diseases [ 22 , 23 ]. It is crucial to adapt the interventions to each collective enhancing the role of primary healthcare settings to overcome those barriers.…”
Section: Other Noncommunicable Diseasesmentioning
confidence: 99%
“…This study is part of a larger research project, entitled "Diagnosis, treatment and follow-up of parasitic diseases (Chagas disease and strongyloidiasis) in the province of Alicante”. The results of the three community-based screening campaigns for strongyloidiasis have recently been reported [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Usage and distribution for commercial purposes requires written permission. was a Dominican Republic native, and a recent study demonstrated a prevalence of 12% in Latin American migrants [7]. Second, in Silva et al [5], the patient, who was immunocompetent, had a suspicious gastric ulcer with upper gastrointestinal bleeding.…”
Section: Palavras Chave Strongyloides Stercoralis • Estrongiloidíase • úLcera Gástrica • Biópsiamentioning
confidence: 95%
“…First, the case presented by Silva et al [5] seems to have an autochthonous origin, something that is now infrequent in the Iberian Peninsula. In contrast, the patient described by Alcázar et al [6]was a Dominican Republic native, and a recent study demonstrated a prevalence of 12% in Latin American migrants [7]. Second, in Silva et al [5], the patient, who was immunocompetent, had a suspicious gastric ulcer with upper gastrointestinal bleeding.…”
mentioning
confidence: 98%